Association of procurement technique with organ yield and cost following donation after circulatory death - Bakhtiyar, Syed Shahyan; Maksimuk, Tiffany E.; Gutowski, John; Park, Sarah Y.; Cain, Michael T.; Rove, Jessica Y.; Reece, T. Brett; Cleveland, Joseph C.; Pomposelli, James J.; Bababekov, Yanik J.; Nydam, Trevor L.; Schold, Jesse D.; et al. (American journal of transplantation, 2024)
Donation after circulatory death (DCD) could account for the largest expansion of the donor allograft pool in the contemporary era. However, the organ yield and associated costs of normothermic regional perfusion (NRP) compared to super-rapid recovery (SRR) with ex-situ normothermic machine perfusion, remain unreported. The Organ Procurement and Transplantation Network (December 2019 to June 2023) was analyzed to determine the number of organs recovered per donor. A cost analysis was performed based on our institution’s experience since 2022. Of 43 502 donors, 30 646 (70%) were donors after brain death (DBD), 12 536 (29%) DCD-SRR and 320 (0.7%) DCD-NRP. The mean number of organs recovered was 3.70 for DBD, 3.71 for DCD-NRP (P < .001), and 2.45 for DCD-SRR (P < .001). Following risk adjustment, DCD-NRP (adjusted odds ratio 1.34, confidence interval 1.04-1.75) and DCD-SRR (adjusted odds ratio 2.11, confidence interval 2.01-2.21; reference: DBD) remained associated with greater odds of allograft nonuse. Including incomplete and completed procurement runs, the total average cost of DCD-NRP was $9463.22 per donor. By conservative estimates, we found that approximately 31 donor allografts could be procured using DCD-NRP for the cost equivalent of 1 allograft procured via DCD-SRR with ex-situ normothermic machine perfusion. In conclusion, DCD-SRR procurements were associated with the lowest organ yield compared to other procurement methods. To facilitate broader adoption of DCD procurement, a comprehensive understanding of the trade-offs inherent in each technique is imperative.